Judicial interpretation of legal texts: a study in Jordanian legislation - Mashal Mufleh Jarrah; Safa Hakem Mestarih; Ghazi Ayed Alghathian (Cogent Social Sciences, 2024)
When applying legal texts to the facts of a case, these texts may conflict with each other, or the conflict may exist in the same text, or they may be obscured or deficient. It is incumbent upon the judge to interpret these texts and remove the conflict, ambiguity, and deficiency in order to reach a judicial ruling based on sound legal texts that align with the provisions of the law. Due to the diversity of types, reasons, and methods for interpreting legal texts, this study aims to clarify judicial interpretation of legal texts and distinguish it from other types of interpretation, along with their reasons and methods. The researchers used a descriptive-analytical approach by describing and analyzing the legal texts related to the subject of the study to reach the desired results. The researchers reached several results and recommendations, the most important of which is that the judiciary plays a key role in interpreting legal texts when applied to the facts presented to it in order to address any deficiencies, ambiguities, or conflicts within those texts. The study recommends establishing a legal system that shows the methods, reasons, and cases for judicial interpretation, in order to address legal texts when applied to the legal facts presented to the judiciary.